Haur Galur Youth Organization Training in Understanding of Basic and Supporting Components of IoT Technology - Erwani Merry Sartika; Daniel Setiadikarunia; Aan Darmawan; Audyati Gany; Novie Theresia BR. Pasaribu; Vincensius Nugroho (Institut Teknologi Nasional, Bandung, 2020)
Internet of Things (IoT) is a conceptual technology that aims to complement the benefits of internet connectivity that connected continuously. IoT is a paradigm that states that each object can be used as a device that can identify, sense, as long as it is connected to the telecommunications network and provides communication with other equipment that connected to the internet. PAR (Participatory Action Research) is a method that involves interested parties in assessing the actions being carried out to make changes for the better. Youth Organization is a place for the development of the young generation that grows from awareness and responsibility, and officially is supported by the government to develop the potential that exists in the area. Electrical Engineering Study Program of Universitas Kristen Maranatha supports Karang Taruna Haur Galur Sukagalih Village, Bandung City, by providing knowledge, competencies, and skills, especially in the Internet of Things technology. Through this training obtained the results that indicate an increase of 30%, specifically about the knowledge of the nature of capacitors, and knowledge of WiFi. While for some knowledge questions such as LDR, pull-up, and some symbols, a quite good correct answer percentage of around 40% (from all participants) was obtained. The motivation of participants to progress and develop is seen from 100% of participants felt training needed to be continued again.